Design of Dispatching Console with unified communications - Alvarez Mederos, Helen María; Anías Calderón, Caridad; Fernández Carcasés, Fidel Alejandro (Telemática, 2023)
Technological obsolescence, added to the demand for new services over existing trunking networks and their users, is required to achieve technological independence to resolve this situation. In functions of it, the article proposes a dispatching console design with unified communications, which allows Voice over Internet Protocol (VoIP English term acronym) and trunking services integration. In addition, the article specifies the applications of reference for the proposed design implementation and the principal requirements to develop the dispatching console. The proposal is validated according to the utilization of two ways: tests over a scenario that simulates some of the required functionalities of the designed dispatching console; and an experts consult, in this case, MoviTel specialists; this company is associated with the implementation and management of eLTE trunking network in Cuba, a reference for the kind of network that is studied on this article; in which case was obtained favorable results.